Perbandingan Relasi Gender Novel “Maransi” Karya A.R. Rizal dan Novel “Re: dan Perempuan” Karya Maman Suherman - Nola Florina (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article aims to describe the results of women's gender analysis and the differences in views of A.R. Rizal and Maman Suherman regarding gender relations in their novels. This article uses a qualitative descriptive method. The object of this research is the novels